EXPLOITATION CHARACTERISTICS OF ZOOBENTHOS RESOURCES WITH ECONOMIC VALUE AT THE NHA PHU WATERS, KHANH HOA PROVINCE, VIETNAM - Ngai, Phan Duc; Tuan, Vo Si; Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2017)
The exploitation characteristics of zoobenthos resources with economic value at the Nha Phu waters were determined by five field trips carried out from 2011 - 2016. The results shows that Nha Phu waters have had great exploitation pressure, with high density of boats (11.9 motorboats/100 ha, 7.7 boats/100 ha and 16.2 people/100 ha), average days of fishery exploitation being high (185 days/fishery/year) and concentrating mainly in the dry season (70% of total average days of fishery/year), specially the destructive artisanal fisheries, (56% of total time of fishery). The average yeild of fishery was dominant in the dry season (73% of total commercial yield and 93% of total number of benthic animal seeds), in which the destructive artisanal fisheries possess 73% of the entire yield of benthic animal. Yields of zoobenthos have decreased seriously, specially for crustaceans (17%). It may be due to greater pressure of fishery exploitation, especially the destructive artisanal fisheries. The results of this study will contribute the scientific basis and data to planning for effective exploitation and management of fisheries resources.